INTERNATIONAL COOPERATION IN THE PROTECTION OF THE INDONESIAN MIGRANT FISHING VESSELS CREW ON TAIWAN-FLAGGED SHIPS - Inasa Hening Sawengi; Najamuddin Khairur Rijal (FISIP Universitas Malikussaleh, 2022)
This study discusses the government's efforts to protect the Indonesian migrant fishing vessels crew on Taiwan-Flagged Ships. The high number of the Indonesian migrant fishing vessels crew has implications for various problems. The absence of a specific law in the protection of Indonesian migrant fishing vessels crew and the disharmony of regulation on the distribution of authority is the core of the problem. The exploitation experienced by Indonesian migrant crews, especially on fishing vessels Taiwan-Flagged ships, is quite high and has not been resolved. The researcher uses the concept of international cooperation and migrant workers to see the government's efforts. The method is qualitative using a descriptive approach through the collection of library research. The results found that the Indonesian government seeks to strengthen bilateral relations with Taiwan, establish cooperation with the International Labour Organization, International Organization of Migration and Interpol in order to ensure the protection of the Indonesian migrant fishing vessels crew.Penelitian ini membahas mengenai upaya pemerintah dalam perlindungan Pekerja Migran Indonesia (PMI) Awak Kapal Perikanan Taiwan. Tingginya pengiriman PMI Awak Kapal terutama dalam sektor perikanan berimplikasi terhadap berbagai permasalahan. Tidak adanya hukum yang spesifik dalam perlindungan PMI-Awak Kapal perikanan serta ketidakharmonisan regulasi pembagian kewenangan merupakan inti dari permasalahan. Eksploitasi yang dialami oleh PMI Awak Kapal terutama pada kapal perikanan milik Taiwan terbilang cukup tinggi dan belum terselesaikan. Peneliti menggunakan konsep kerja sama internasional dan migrant workers untuk melihat upaya pemerintah. Adapun metode penelitian ini adalah kualitatif dengan menggunakan pendekatan deskriptif melalui pengumpulan data studi kepustakaan. Hasil penelitian menemukan bahwa pemerintah Indonesia berupaya melakukan penguatan hubungan bilateral dengan Taiwan, menjalin kerja sama dengan International Labour Organization, International Organization of Migration, dan Interpol dalam rangka memastikan perlindungan terhadap PMI Awak Kapal Perikanan.